DISPLAYING THE POLYTEMBRALITY OF THE ORCHESTRA OF UKRAINIAN FOLK INSTRUMENTS WHEN ARRANGED FOR ACCORDION "UKRAINIAN FANTASY" YAROSLAV OLEKSIV - Oleksiv Halyna Vasylivna (International Journal of Innovative Technologies in Social Science, 2021)
Over the past decade, the arsenal of original compositions for the accordion has considerably expanded, but a significant place among the performing repertoire is the genre of translation of works from the repertoire of other instruments, ensembles or orchestras for the accordion. Since the translation of the orchestral repertoire with account of the timbre features of the accordion, has not yet become the subject of musicology research, the task is to elucidation of the main principles of this genre. The combined analysis of translations and executive-methodical recommendations become the basis for a deep understanding of the ideological conception, stylistic features and rethinking of the timbre transformations, and therefore the quality of the performance of the work itself.Translation works for the accordion from the repertoire of the Ukrainian folk instruments orchestra has favorable conditions for many parameters, as demonstrated by Y. Oleksiv "Ukrainian fantasy". The timbre specificity - the existence of a large number of different instrumental groups and voices in the orchestra is successfully transmitted in the accordion translation due to a number of timbre registers of the instrument, the diversity of which allows the most complete transfer of orchestral coloration. The author takes into account the slight difference in the sound of the right and left keyboards of the accordion and demonstrates it in an advantageous applying for translation, creating the effect of a multi-timbre "dialogue". The techniques of playing on the accordion fully reproduce the dynamic gradations of the orchestral sound, as the characteristic feature of such orchestra is a chamber. The author simulates the techniques of sound formation and the specifics of various orchestral instruments. The bandura pinch, the overtones dulcimer "echo", the reed pipe glissando, the violin detache and the articulation variety of instrumental composition of the orchestra composer transmits using a detail palette. Perfect constructive features of the accordion allow you to successfully adapt the multi-layer orchestra texture. In the accordion translations of orchestral compositions, the epic and poetics of folk melodies are transmitted as clearly as possible. This work is aimed at deeper understanding of the content and expressiveness of translated works by the performers. The research can be an impetus for transmissions and their research on the repertoire of the chamber ensemble for the accordion, as well as the translation of pieces for the accordion.